2010
DOI: 10.1007/s12010-010-8951-y
|View full text |Cite
|
Sign up to set email alerts
|

Value-Added Production of Nisin from Soy Whey

Abstract: The objective of this study was to evaluate the potential of low/negative value soy whey (SW) as an alternative, inexpensive fermentation substrate to culture Lactococcus lactis subsp. lactis for nisin production. Initially, a microtiter plate assay using a Bioscreen C Microbiology Plate Reader was used for rapid optimization of culture conditions. Various treatments were examined in efforts to optimize nisin production from SW, including different methods for SW sterilization, ultrasonication of soy flake slu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Also, cull potatoes, the unacceptable version of potato tubers, cannot support the growth of L. lactis alone, but as part of a supplemented media, the simultaneous production of bacteriocins and lactic acid was optimized (Liu, Liu, & Chen, ). Soy whey, a residue from the isolation of soy proteins, demonstrated to achieve higher yields in bacteriocin production compared to other dairy and nondiary supplemented media, even when it only contains 2.2% of protein (Mitra et al., ). ACE‐inhibitory activity was observed in bioactive peptides generated by the proteolytic strain Lactobacillus acidophilus in a supplemented soy whey media (Fung & Liong, ).…”
Section: Selection Of the Protein‐based Mediamentioning
confidence: 99%
“…Also, cull potatoes, the unacceptable version of potato tubers, cannot support the growth of L. lactis alone, but as part of a supplemented media, the simultaneous production of bacteriocins and lactic acid was optimized (Liu, Liu, & Chen, ). Soy whey, a residue from the isolation of soy proteins, demonstrated to achieve higher yields in bacteriocin production compared to other dairy and nondiary supplemented media, even when it only contains 2.2% of protein (Mitra et al., ). ACE‐inhibitory activity was observed in bioactive peptides generated by the proteolytic strain Lactobacillus acidophilus in a supplemented soy whey media (Fung & Liong, ).…”
Section: Selection Of the Protein‐based Mediamentioning
confidence: 99%
“…used whey as a substrate for Lactobacillus plantarum , aiming to produce a potential fermented beverage from soy, with sanitary and nutritional improvements. Mitra et al 94 . studied the production of nisin, an antibacterial peptin produced by Lactococcus lactis .…”
Section: Resultsmentioning
confidence: 99%
“…Soy whey, one of the liquid by-products generated during tofu preparation, is becoming a point of concern for soybean processing industry. Mitra et al (2010) reported that production of soy protein isolate results in generation of soy whey (chemical oxygen demand [COD], 25,000 mg/L) equivalent to one-third of the initial raw material. Thus, a huge economic penalty is borne by the industry due to its disposal cost.…”
Section: Introductionmentioning
confidence: 99%
“…Mitra et al . () reported that production of soy protein isolate results in generation of soy whey (chemical oxygen demand [COD], 25,000 mg/L) equivalent to one‐third of the initial raw material. Thus, a huge economic penalty is borne by the industry due to its disposal cost.…”
Section: Introductionmentioning
confidence: 99%